O sertão potiguar comunica: midiatização e práticas sociais. Ou como a recepção da pauta política se desdobra em práticas sociais em Pau dos Ferros - Sena, Patrícia Rakel de Castro (2011)
This dissertation is the result of the development of a two-year research entitled POTIGUAR ACROSS THE COMMUNICATION: MEDIATIZATION AND SOCIAL PRACTICES. Or as the reception of the political agenda unfolds in social practices of the Pau dos Ferros, showwing Pau dos Ferros as a provincial oestano of Rio Grande do Norte, now living a meaningful set of social transformations, which interact with practices media that have just mediatized new public policies in the area of Technical Education and Higher Education. Thus, with the introduction and expansion of state and federal public policy of democratization of Technical and Higher Education in the period 2002 to 2010, the phenomenon of migration of students from elementary and high school, before existing in the region has changed significantly in that Pau dos Ferros polo is made. The concentration of the media city in the hands of politicians, in their favor, and the emergence of new midiatizações are contributed to the formation of this (non-migration) and other social practices, reinventing and rearranging the schedule of the ideas and concepts about the educational practices. Our goal is to observe the relationship of interaction between media, politics and education and examine how young students are realizing this interaction. Under the prospects of receiving the light of Cultural Studies, strolling our research primarily on the technique of focus group data collection